Biodegradation of Azo and disperse dyes by Trametes versicolor: Process optimization and MnP enzyme dynamics - Isma Fayyaz; Salina Saddick; Raja Tahir Mahmood; Muhammad Javaid Asad; Muhammad Altaf Hussain; Jiandong Hu; Muhammad Awais; M. Ijaz Khan; Shaxnoza Saydaxmetova (Results in Engineering)
Textile industries are the major source of environmental pollution in the world because they release dyes, chemical and pigments in wastewater which are produced during dying process. The current study was designed with aims of screening Trametes versicolor biodegradation potential for four selected textile dyes i.e. direct pink B, direct yellow BG, dispersed red S3B and disperse yellow SRLB. The process was further optimized by implying Response Surface Methodology (RSM) under Central Composite Design (CCD). The effect of manganese peroxidase (MnP) on the biodegradation was also monitored and it was partially purified as well as characterized. The screening experiments showed that this fungus has higher biodegradation potential for direct dyes (pink B = 58.9 % & yellow BG= 54.6 %) compared to disperse dyes (redS3B= 43.12 % & yellow SRLB= 27 %). The biodegradation of direct dyes was increased to 72.46 % & 93.29 % (pink B) and 84.69 % & 87.42 % (yellow BG) after two optimization steps. Study of manganese peroxidase (MnP) confirmed its active role in biodegradation with increasing its activity from 145 IU/mL/min to 194 IU/mL/min and from 188.5 IU/mL/min to 201.6 IU/mL/min during biodegradation of direct pink B & yellow BG, respectively. The MnP was partially purified in the presence of 60 % ammonium sulfate and it showed optimum pH= 4 and temperature 30 °C. The MnP of T. versicolor is quite active (Vmax= 60.24 mM/mL/min) ligninolytic enzyme and has good affinity for guaicol (Km=8.58 µM).